2019
DOI: 10.31463/aicusbed.586485
|View full text |Cite
|
Sign up to set email alerts
|

Mi̇zah Temelli̇ Etki̇nli̇kleri̇n 7. Sinif Öğrenci̇leri̇ni̇n Yazma Beceri̇leri̇ne Etki̇si̇

Abstract: Turkish Education Program were taken into consideration. The study was enriched with memories, funny stories, cartoons and funny short films. The "Written Expression Evaluation Form" in the Turkish Education Program was used to collect the research data. The analysis of this data was done in SPSS 15.0 package program. According to the results of the post-test, a significant difference was found between the two groups in favor of the experimental group. According to the findings and the results, various suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…In addition to the contribution of humor in social emotional areas, there are many studies on its contribution to academic achievement. For example, Kılıç & Şakiroğlu (2019) found that humor-based activities were effective on the writing skills of 7th grade students. In Lovorn & Holaway's (2015) study, teachers at different levels from kindergarten to high school stated that humor in the classroom "occurs in an instant", that it is a way to ensure learning, and that humorous activities are effective in gathering students' attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the contribution of humor in social emotional areas, there are many studies on its contribution to academic achievement. For example, Kılıç & Şakiroğlu (2019) found that humor-based activities were effective on the writing skills of 7th grade students. In Lovorn & Holaway's (2015) study, teachers at different levels from kindergarten to high school stated that humor in the classroom "occurs in an instant", that it is a way to ensure learning, and that humorous activities are effective in gathering students' attention.…”
Section: Introductionmentioning
confidence: 99%
“…Öğrencinin yazacağı konuya, yazacağı hedef kitleye uygun olarak yazma amacını belirginleştireceği bir aşama olarak yazma konusuna karar vermesiyle başlayan, hazırlık, planlama, düzenleme, düzeltme ve paylaşma gibi aşamalardan oluşan bir süreci gerektirir. Yazının çerçevesinin belirlenerek, cümleler arasında akıcılığı, tutarlılığı ve bağdaşıklığı ise yazma becerisine sahip bireylerin yazarken dikkat etmesi gereken özellikler arasında sayılabilir (Sever & Memiş, 2013).…”
Section: Introductionunclassified